In Silico Exploration of Plant Extracts as Ache Inhibitors: Insights from Molecular Dynamics and Mm/Gbsa Analysis for Alzheimer's Drug Development - Kurt, Barıs; Evcil, Murat; Baran, Ayşe (My University, 2025)
Alzheimer's disease is a long-term neurological disorder that affects memory and other cognitive abilities. Physostigmine is a drug still used in treating symptoms associated with this disease, with its primary mechanism of action being AChE inhibition. AChE plays a crucial role in cholinergic neurotransmission, and its inhibition has been linked to the improvement of symptoms in Alzheimer's disease. In this study, 34 phytochemicals detected through LC-MS/MS analysis of 13 plant species were investigated as potential alternative drug candidates to physostigmine. For this purpose, docking studies followed by molecular dynamics simulations and MM/GBSA energy calculations were performed. The results revealed that 24 out of 34 phytochemicals were either very close to physostigmine (MM/GBSA binding affinity: -26.102 kcal/mol) or better AChE inhibitors. Additionally, it was determined that physostigmine increased the flexibility of the molecule when bound to the AChE enzyme, a unique result compared to our drug candidates. Our research emphasizes the potential of plant-derived compounds as AChE inhibitors and presents promising candidates for future drug development studies. Furthermore, physostigmine's property of increasing enzyme flexibility offers a new perspective in drug design and indicates that the role of this feature in therapeutic efficacy needs to be examined in more detail.
Keywords: MM/GBSA, Medicinal plants, In silico, Drug development